Children’s stories: Reality and cultivation - Nurmanita, Tiara Sevi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
The purpose of this study is to examine the reality and cultivation of children's stories by children and adults. Children's stories used in this study are children's novels. The method used is literary analysis in the form of a mimetic approach. Data sources are in the form of text excerpts from children's novels by children and adults. The results of the study are a comparison of reality and story development in children's novels by children and adults. In terms of reality, it is found that children's stories are imitations of children's real life interpretations as reviewed in children's characteristics. When viewed from the perspective of cultivation, children's stories written by children have simpler storyline, use many conversational texts and tend to use simple sentences. On the other hand, the storylines and sentences in children's stories written by adults are more complex, although the vocabulary used is still simple.